The Development of Decision Support System For The Selection of Outstanding Teachers - Kholis Hermawan; Hendra Dea Arifin; Elvanisa Ayu Muhsina; Nurochman Nurochman (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2014)
The Selection of Outstanding Teachers is an agenda of Department of Education Youth and Sports (Disdikpora) intended to encourage motivation, dedication, loyalty and professionalism of teachers, the expected positive impact on performance improvement. In general elections outstanding teachers have been running smoothly according to specified criteria. However, its implementation is still not optimal felt so necessary to improve, especially in the aspects of assessment. In the assessment of the current selection are inconsistent because one of the criteria assessment (portfolio) that have different valuation range. This makes the need for a decision support system that is able to provide consistency with the application of the normalization judgment and able to show the rank results of the selection.Decision support system used in this research is Simple Additive Weight (SAW) and the Analytic Hierarchy Process (AHP). Both methods support the assessment criteria and weighting. The criteria used for the assessment refer to the Outstanding Teacher Selection Handbook 2012 and based on the results of data analysis assessment Outstanding Teacher Selection of Junior High School, Senior High School and Vocational High School in 2012. The method for developing the system that used in this research is waterfall method.The system is capable of displaying two alternative rank outstanding selection of teachers based on the SAW and AHP methods. These results sorted from the highest alternative to the lowest alternative outcomes. These results are also presented in the form of trend graphs to compare the results of each method. This system is useful to provide a reference for the field of PPTK Disdikpora particularly relevant in decision-making to determine the selection of outstanding teachers. Based on the results of testing the system's functionality, 96.7% stated functionality of the system running well. While the results of the testing interface, 38.96% for Strongly Agree, and 48.05% Agree.